2013
DOI: 10.7726/jtafd.2013.1002
|View full text |Cite
|
Sign up to set email alerts
|

Stability-Indicating HPLC Method for the Determination of Mometasone Furoate, Oxymetazoline, Phenyl Ethanol and Benzalkonium Chloride in Nasal Spray Solution

Abstract: A sensitive stability-indicating reversed-phase high performance liquid chromatographic method was developed for the simultaneous determination of mometasone furoate (MON), oxymetazoline (OXY), phenyl ethanol (PEL) and benzalkonium chloride analogs (BKC1and BKC2) in nasal spray solution. The chromatographic separation was achieved on Cosmosil CN 150 mm x 4.6mm, 5 um column Using a mobile phase consisting of 50 mM KH2PO4 and Acetonitrile in the ratio of 60:40 (v/v), at a flow rate of 2.0 ml/min. The column comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…Moreover, it acts locally in the lung as a bronchodilator [4]. The literature survey reveals that several analytical methods have been published for the estimation of MOM alone and in combination with other drugs like fusidic acid [5], oxymetazoline [6] terbinafine HCl, nadifloxacin [7], eberconazole nitrate [8], miconazole, hydrocortisone [9], ketoconazole [10], salicylic acid [12] etc. Some of these methods include HPLC, GC, supercritical fluid chromatography and UV spectrophotometry.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it acts locally in the lung as a bronchodilator [4]. The literature survey reveals that several analytical methods have been published for the estimation of MOM alone and in combination with other drugs like fusidic acid [5], oxymetazoline [6] terbinafine HCl, nadifloxacin [7], eberconazole nitrate [8], miconazole, hydrocortisone [9], ketoconazole [10], salicylic acid [12] etc. Some of these methods include HPLC, GC, supercritical fluid chromatography and UV spectrophotometry.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed literature survey for methylparaben, mometasone furoate and eberconazole nitrate revealed that determination of individual compound or combination with other drugs have been reported by HPLC [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , LCMS [17][18] , electrophoresis 19 and spectrophotometric method 20 .…”
mentioning
confidence: 99%
“…A number of analytical methods have been reported for the estimation of BKC in various products including ophthalmic preparations [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, there was no method available for estimation of BKC in azelastine hydrochloride ophthalmic formulations.…”
Section: Introductionmentioning
confidence: 99%